Mechanical properties of endodontic posts - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
This study aims to determine the stiffness, elastic limit and strength of selection of endodondic posts recently introduced on the market. Endodontic posts of ceramic (Finesse(TM), Dentsply), zirconia (Cosmopost(TM), Ivoclar Vivadent) and fiber reinforced composite post (FRC Postec(TM), Ivoclar Vivadent) were cemented in a metal block and loaded an angle of 45degrees in an Instron type Testing Machine. From the recorded force-deflection curves the three mechanical properties were determined. The results show that considerable differencies exist with respect to mechanical properties between the investigated newer types of endodontic posts. The ceramic endodontic post (Finesse(TM)) had the lowest values of strength and elastic limit but the stiffness values of Finesse(TM) posts were between Cosompost(TM) and FRC(TM). The FRC(TM) post had the lowest values of stiffness but intermediate values of strength and elastic limit. The Cosmopost(TM), had the highest strength, limit and stiffness values of all the posts investigated.
Keywords: endodontic posts; ceramic post; zirconia; fiber post